Factors That Influence Green Practices Adoption Amongst Logistics Services Providers - Mohd Rizaimy Shaharudin; Jamaludin Akbar; Nurdiyana Nazihah Zainal; Siti Fairuza Hassam; Amir Imran Zainoddin; Muhamad Fadli Mohamad Nizam (International Journal of Supply Chain Management, 2018)
The purpose of this study is to identify the factors that influence the green practices adoption amongst third party logistics services providers in Penang, Malaysia. The factors used in the study included technology (relative advantages, compatibility, and complexity), organisation (organisational support and quality of human resources), and environment (stakeholder pressure, governmental support, and environmental uncertainty). Purposive sampling has been used as the sampling method in this study. The data gained from the questionnaires have been analysed using SmartPLS 3.0 software. The findings show that relative advantages, compatibility, organisational support, quality of human resources, stakeholder pressure, and governmental support influences the green practices adoption. On the other hand, complexity and environmental uncertainty were found to have insignificant impacts towards the green practices adoption. The outcome of this study demonstrates practical implications for the managers by providing evidence of the critical factors to adopt the green practices amongst the third-party logistics services providers.